Manual Material Handling - Moch. Ilman Fauzi (International Research & Development for Human Beings (IRDH), 2024)
Biomechanics is a science that uses the laws of physics and engineering mechanics to be able to examine movements in the body and the effects of forces and moments that occur. Among biomechanical studies, manual material handling (MMH) activities are still considered critical. This research is a research using the method of literature study or literature review. Manual material handling (MMH) is an activity that is done every day by humans. The use of human labor in various activities that are done manually is still very dominant. MMH activities that include lifting, lowering, pushing, pulling have the potential to cause work accidents.